Analysis on the Utilization of Digital Application as the Covid-19 Mitigation Effort - Sunandar Said; Mardhatillah Mardhatillah; Muhammad Rusdi; Herick Herick; Mega Aprisna Arif; Nurul Wakyah; Dwi Erma Kusumawati (Poltekkes Kemenkes Palu, 2023)
Covid-19 has an obvious impact on people's lives. Therefore, the government continues to make efforts to suppress and reduce the negative impacts. One of the efforts being made is to develop the pedulilindungi application to make it easier to track Covid-19 cases. However, the problem that occurs is the lack of utilization of the pedulilindungi application by the public. This study aims to analyze the effect of technology acceptance and technology readiness on the level of utilization of the pedulilindungii application as a Covid-19 mitigation effort. This was a quantitative study with a survey method. This study was conducted from June to August 2022. The population in this study were lecturers, staffs and students within the Muhammadiyah University of Sidenreng Rappang as many as 3394. The study samples were selected using random sampling technique with a target of 358 respondents. Data were collected using a questionnaire based on the technology readiness index (TRI) to assess the level of technology readiness and the Technology Acceptance Model (TAM) to assess the level of technology acceptance. Furthetmore, the data were analyzed using Path Analysis to determine the direct effect and variables of Technology Acceptance and Technology Readiness on mitigation effort, as well as the indirect effect through perception towards the Covid-19 policy. The study results showed that the values of the direct effect of Technology Acceptance and Technology Readiness variables on mitigation efforts were 0.228 and 0.095, respectively, while the indirect effect through the perception towards Covid-19 policy perception were 0.479 and 0.115, respectively. Thus, it was revealed that there wolud be an increase in the effect of Technology Acceptance and Technology Readiness on mitigation efforts if they were supported by government policies. It can be concluded that Technology Acceptance and Readiness had a significant effect on mitigation efforts through the use of the Pedulilindungi application supported by perception towards the Covid-19 policy.